Los métodos de María Montessori en el ámbito de relaciones lógico matemáticas de los niños y niñas del subnivel 2 de educación inicial. - Borja Chuchico, Lucía del Carmen (2021)
This research allowed to strengthen the logical-mathematical relations area through Maria Montessori's methods in children sublevel 2 of early education at Vicente Leon School, daily life is full of mathematical aspects, everyday activities require concentration, accuracy and balance; the research purpose was to achieve educational development through experience and experimentation, proposing playful and creative activities to work on mathematical concepts and strategies to innovate the learning process, starting from the concrete to the abstract. This research development was applied a methodology with a mixed quantitative-qualitative approach, the data collected was used to analyze and perform the information from a contextual and objective way point of view, the data obtained show the positive result achieved after the application of an effective and didactic proposal of Maria Montessori's methods for the development of mathematical logical skills in children; through the application of interesting and innovative strategies, children developed their senses, motor skills, attention, concentration and skills to encourage their autonomy, allowing the children the free construction of their knowledge and independence in their social environment, making this proposal a fascinating way of learning.